2018
DOI: 10.1016/j.bbapap.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside lipids accelerate α-synuclein amyloid formation

Abstract: The deposition of α-synuclein fibrils is one hallmark of Parkinson's disease. Here, we investigate how ganglioside lipids, present in high amounts in neurons and exosomes, influence the aggregation kinetics of α-synuclein. Gangliosides, as well as, other anionic lipid species with small or large headgroups were found to induce conformational changes of α-synuclein monomers and catalyse their aggregation at mildly acidic conditions. Although the extent of this catalytic effect was slightly higher for gangliosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 81 publications
(115 reference statements)
2
65
1
Order By: Relevance
“…The mildly acidic pH is relevant to some cellular environments, such as endosomes and lysosomes. At these conditions, ganglioside-containing membranes have also been shown to trigger the aggregation of the amyloid protein α-synuclein, which is associated with Parkinson's disease [8,36]. For practical reasons, the overall lipid concentration varies between experiments using different methods, so an overview of the concentrations and molar ratios in all samples investigated is given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mildly acidic pH is relevant to some cellular environments, such as endosomes and lysosomes. At these conditions, ganglioside-containing membranes have also been shown to trigger the aggregation of the amyloid protein α-synuclein, which is associated with Parkinson's disease [8,36]. For practical reasons, the overall lipid concentration varies between experiments using different methods, so an overview of the concentrations and molar ratios in all samples investigated is given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to the example highlighted in the introduction, that ganglioside-containing lipid systems can cause an acceleration in the amyloid aggregation of α-synuclein, we can speculate on some aspects of the system that may indeed influence the interaction between this protein and the lipid assemblies. It has been shown that α-synuclein adsorbs to lipid membranes and micelles with a negative charge [36,[75][76][77]. In the adsorbed state, the protein forms an α-helix at the membrane/micelle interface [36,75,78], and membranes covered with proteins are also a trigger for the aggregation process [36,75].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations